Strategi Cerdas Pengelolaan Dana BOS dalam Membangun Branding Lembaga Pendidikan Islam sebagai Basis Daya Saing Institusional: Strategi Cerdas Pengelolaan Dana BOS dalam Membangun Branding Lembaga Pendidikan Islam sebagai Basis Daya Saing Institusional - Usni; Hamdi Abdul Karim (Ikhtisar: Jurnal Pengetahuan Islam, 2026)
This study aims to analyze smart strategies in managing School Operational Assistance (BOS) funds as a foundation for building the branding of Islamic educational institutions with competitive advantage. The focus of the study lies in planning, allocation, and implementation of financing that can generate specific institutional strengths as a distinctive identity. This research employs a qualitative approach with a library research method by reviewing relevant literature on educational financial management, development of flagship programs, and institutional branding in Islamic education. The findings indicate that well-structured planning, focused budget allocation on priority programs, and consistent implementation can produce tangible institutional excellence. These strengths subsequently transform into institutional branding that enhances public trust and attractiveness, particularly in the digital era. The integration of financial management and institutional identity development contributes significantly to the advancement of Islamic education management in a more strategic and value-oriented direction. This study is expected to serve as a reference for educational managers in designing innovative, effective, and sustainable financing policies.